Nanofiber oil-gas separation membrane material with mechanical regeneration function and preparation method thereof

By blending polymers with positron affinity and negative electron affinity and electrospinning to prepare nanofiber membranes, the problem of insufficient filtration efficiency, pressure drop balance and service life of nanofiber oil and gas separation membrane materials in the prior art is solved, and an efficient and long-life oil and aerosol filtration effect is achieved.

CN119565387APending Publication Date: 2025-03-07TIANJIN POLYTECHNIC UNIV +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411849211.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing nanofiber oil and gas separation membrane materials are difficult to balance between filtration efficiency and pressure drop, and the filter has a short service life, especially in large-area application scenarios.

Method used

The nanofiber membrane is prepared by electrospinning technology to improve the electrostatic density of the fiber surface and the regeneration of charge is achieved through mechanical charging.

Benefits of technology

It significantly improves the filtration efficiency of nanofiber membranes on oil and aerosols, extends the service life of the filter, and is suitable for a variety of filtration systems, including industrial ventilation systems and personal protective equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation method of a nanofiber oil-gas separation membrane material with a mechanical regeneration function, which comprises the following steps: 1) preparing a polymer solution: dissolving two or more than two polymers in an organic solvent to obtain the polymer solution; the polymer comprises a positive electron affinity material and a negative electron affinity material; and 2) preparing the nanofiber membrane: performing electrostatic spinning, melt-blowing, solution airflow assistance, template synthesis, self-assembly or microphase separation on the polymer solution to obtain the nanofiber membrane. The polymer mixed solution is prepared into the single-layer nanofiber membrane with the endogenous triboelectric effect through the technologies such as electrostatic spinning, and the charge of nanofibers is remarkably increased. The nanofiber membrane does not need complex structural design, high-efficiency removal efficiency and reusability of the oil mist are achieved, and the device is suitable for a large-scale industrial ventilation system or environment-friendly equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane materials, and in particular relates to a nanofiber oil-gas separation membrane material with mechanical regeneration function and a preparation method thereof. Background Art

[0002] Oil mist generated in production and life can reduce air quality, affect human health and damage machines. Therefore, effectively removing oil mist from the air is of great significance to production and life. At present, commercial oil mist filters cannot effectively remove fine oil particles (diameter <1 μm). Although changing the structure or surface wettability of the filter can increase the filtration efficiency, the pressure drop will also increase more significantly. Nanofiber membranes prepared by electrospinning have broad application prospects in oil mist filters because of their flexibility, low cost, small pore size and high porosity, showing high removal ability for small oil particles. However, most nanofiber membranes still have a high pressure drop, and the filtration efficiency will also decrease with the increase of filtration time. Therefore, achieving high efficiency, low resistance and long service life of oil mist filters remains a major challenge.

[0003] The electrostatic effect is believed to be able to effectively solve the problem of balancing filtration efficiency and pressure drop. By increasing the static charge on the fiber surface, the filtration efficiency can be effectively improved without increasing the pressure drop. Although traditional electret filters believe that the electrostatic attraction of oil mist is small, recent studies on electret non-woven fabric filtration have shown that static charge has a significant enhancing effect on the removal of oil mist. For example, some studies add masterbatch to meltblown fibers to increase the static charge, thereby improving the filtration efficiency of oil mist, but the shedding of the masterbatch will lead to a decrease in filtration efficiency. In addition, a key issue of the electrostatic effect in oil mist filtration is charge dissipation, which will reduce filtration performance. In this regard, the introduction of the triboelectric principle into the nanofiber membrane to achieve charge regeneration can maintain the high filtration efficiency of the nanofiber membrane for oil mist and improve its recyclability. However, the regenerated charge of the existing triboelectrically charged nanofiber membrane only shows a gain effect on the filtration of salt particles, and there is no improvement in the filtration of oil particles.

[0004] Increasing the amount of static charge in the electret filter can effectively improve the air filtration efficiency and extend the service life of the filter. However, the current methods for increasing the charge of the filter include optimizing the parameters of the corona electret and hydroentanglement / needle-punch friction electret, but the corona electret has problems of charge instability and environmental damage, while the friction electret has a high cost and limited charge improvement. Electrospinning technology can also generate induced charges on the fiber surface, but this technology usually uses a single polymer to prepare nanofiber membranes, resulting in a limited amount of charge carried. Although the addition of organic fillers or inorganic nanoparticles can increase the surface charge of nanofibers, the uneven distribution of fillers will have a great impact on the filtration efficiency. The biggest problem facing the electret nanofiber filter is that the filtration efficiency decreases rapidly as the static charge dissipates in the environment. Therefore, the introduction of regenerative charge based on the triboelectric principle into the nanofiber membrane can maintain the high filtration efficiency of the fiber filter and improve the recyclability. However, the self-generated charge effect of the existing friction electret fiber filter is extremely dependent on the design and optimization of the layered structure. In addition, these filters are insufficient in filtering capacity when facing large-area application scenarios, such as ventilation systems in factories, hospitals and other places. The electret filter combined with friction can restore its significant filtering efficiency for solid particles. However, the filtering effect for liquid particles is not ideal. So far, there is no literature or patent report mentioning whether it is possible to use strong electret properties to achieve efficient filtration of oil aerosols, and whether the filtering efficiency of electrets for oil aerosols can be restored through friction.

[0005] At present, many patents and documents have disclosed the progress of air filtration nanofiber membranes based on triboelectric effect. For example, a Chinese patent (application number: CN202280081745.8; publication number: CN118451226A) introduces a high-porosity polylactic acid high-efficiency air filtration membrane based on triboelectric effect, which has a long-term high filtration efficiency (99.5%) for 0.3 μm NaCl particles. Another Chinese patent (application number: CN202280024078.X; publication number: CN117083425A) introduces an energy collection fabric for electrostatically enhanced filtration of particulate matter. Another Chinese patent (application number: CN202210082584.6; publication number: CN114504951A) introduces an electret filter membrane and its preparation method, which realizes charge regeneration and reuse by rolling water droplets and triboelectrically cleaning the surface of the filter membrane after dust retention, and then drying it. Wang et al. incorporated PVDF nanofiber membrane and copper foil into the mask. The solid aerosol removal efficiency of the modified mask was 86.9% and the pressure drop was 57 Pa. When wearing a mask, breathing will generate triboelectric charges, thereby extending the service life. (Liu G, Nie J, et al. Self-Powered Electrostatic Adsorption Face Mask Based on a Triboelectric Nanogenerator. ACS Applied Materials & Interfaces 2018, 10 (8): 7126-7133.). Hu et al. introduced a wearable smart filter based on the triboelectric mechanism, with a filtration efficiency of 99% for salt particles. The triboelectric charges generated by breathing significantly enhanced the accumulation of charges. (Shuo Shi, Jinlian Hu et al. An Intelligent Wearable Filtration System for Health Management. ACS Nano 2023 17 (7), 7035-7046).

[0006] However, at present, there is no patent disclosure related to the nanofiber oil-gas separation membrane material technology with mechanical regeneration function. Based on this, the present application was developed. Summary of the invention

[0007] The present invention aims to overcome the defects of the prior art and provide a nanofiber oil-gas separation membrane material with mechanical regeneration function. The material adopts two polymers with positive electron affinity and negative electron affinity, mixes them in the same solution, and prepares a nanofiber membrane by electrostatic spinning and other technologies. The obtained nanofiber membrane can enrich static charge in large quantities. Due to the large difference in surface energy between the two polymers, one polymer material (such as the positive electron affinity material) tends to be distributed inside the fiber, while the other polymer (such as the negative electron affinity material) is concentrated on the surface of the fiber. The interaction between the two polymers will cause a larger dipole moment, and the uneven distribution of the two materials in the fiber skin and core makes one charge tend to be distributed on the surface and the other charge is distributed inside, thereby greatly improving the static density on the fiber surface. In addition, by regulating the ratio of the two polymers inside the fiber, the charge on the fiber surface can be further increased, so that the nanofiber membrane shows a higher filtration efficiency for oil aerosol.

[0008] The present invention also provides a method for preparing the nanofiber oil-gas separation membrane material with mechanical regeneration function.

[0009] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a nanofiber oil-gas separation membrane material with mechanical regeneration function comprises the following steps: 1) Preparing a polymer solution: dissolving two or more polymers in an organic solvent to obtain a polymer solution; the polymers include a positron affinity material and a negative electron affinity material; 2) Preparation of nanofiber membrane: The polymer solution is prepared by electrospinning, melt blowing, solution airflow assistance, template synthesis, self-assembly or microphase separation to obtain the nanofiber membrane.

[0010] Specifically, the positron affinity material includes but is not limited to one or more of polysulfone, nylon, cellulose, etc.; the negative electron affinity material includes but is not limited to one or more of polyvinylidene fluoride, polypropylene, polyacrylonitrile, etc. Further, the mass ratio of the positron affinity material to the negative electron affinity material can be 10:0-0:10.

[0011] Specifically, the organic solvent may be a mixture of N,N-dimethylformamide (DMF) and tetrahydrofuran (THF); the volume ratio of N,N-dimethylformamide to tetrahydrofuran may be 10:0-0:10. The solvent is mainly used as a dissolving medium to dissolve the polymer.

[0012] Furthermore, in step 1), the concentration of the polymer solution can be 1-70%. The dissolution temperature of the polymer is between 0-100°C, and the higher the temperature, the faster the dissolution. The polymer can also dissolve at room temperature, preferably 60°C.

[0013] Furthermore, in step 2), the electrospinning is specifically as follows: the nanofibers are collected using a roller collector, and during the electrospinning process, the applied voltage, the flow rate of the polymer solution and the spinning distance are between 1-50 kV, 1-5 mL / h and 1-20 cm, respectively. The thickness of the nanofiber membrane is between 10 μm-1 mm, and the electrospinning is carried out under environmental conditions of a temperature of 10-65°C and a relative humidity of 10-50%, and the electrospinning time is 1-5 h.

[0014] The invention provides a nanofiber oil-gas separation membrane material with mechanical regeneration function prepared by the preparation method.

[0015] The present invention also provides a method for regenerating the nanofiber oil-gas separation membrane material with mechanical regeneration function, which comprises: repeatedly compressing the nanofiber membrane under the conditions of a pressure of 1-100 N and a frequency of 1-100 Hz for a compression time of 0.1-1 h.

[0016] Furthermore, when the surface of the nanofiber membrane is adhered with oily substances, the nanofiber membrane may be preferably rinsed with ethanol 10-100 times in advance, and then dried at room temperature and compressed repeatedly.

[0017] The key points of the technology of this application are described in detail below: 1. Basic material design principle: A new method that significantly enhances the charge enrichment ability of nanofibers by blending two or more polymers, so that the charge intensity carried by the nanofibers is sufficient to produce a strong electrostatic effect on the oil aerosol contained in the surrounding airflow, thereby intercepting and capturing it, achieving the purpose of effective filtration while maintaining a low filtration resistance.

[0018] 2. Principle of surface potential enhancement: One polymer has a greater affinity for positive charges, while the other polymer has a greater affinity for negative charges, and the two polymers have a large difference in surface energy. During the preparation process, the two materials are blended, resulting in a greater dipole effect. During the fiber-forming process, one material is mainly concentrated on the outer surface of the fiber, while the other polymer is concentrated inside the fiber, so that the surface is enriched with a single charge, and the inside is enriched with charges opposite to the fiber surface, thereby increasing the potential of the fiber surface and enhancing its oil aerosol filtration performance.

[0019] 3. Specific polymer materials used: materials with positive electron affinity and negative electron affinity, including positive electron affinity materials such as polysulfone, nylon, cellulose, and negative electron affinity materials such as polyvinylidene fluoride, polypropylene, and polyacrylonitrile. This material pairing helps to generate and maintain static charge.

[0020] 4. Polymer ratio and concentration range: The mass ratio of the two blended polymers in the material ranges from 10:0 to 0:10, and the polymer solution concentration ranges from 0.1% to 90% (preferably 1-70%), which provides a flexible formulation design space for the preparation of the material.

[0021] 5. Nanofiber diameter and fiber membrane thickness: The diameter of nanofibers ranges from 1 nm to 1000 nm, and the thickness of nanofiber membranes ranges from 10 μm to 1 mm. This makes the material suitable for all filter types including primary, medium and high efficiency filters.

[0022] 6. Fiber preparation technology: The technologies for preparing blended polymer fibers include electrospinning, melt blowing, solution airflow assistance, template synthesis, self-assembly and microphase separation, which provide diverse methods for manufacturing high-performance nanofibers.

[0023] 7. The structure of nanofiber membrane and its matching with other materials: The structure of nanofiber membrane includes common and uncommon structures such as single-layer structure, multi-layer structure and pleated structure; nanofiber membrane can form a composite filtration system with other filter materials or filter frames. These characteristics help nanofiber membrane adapt to the structural components and filtration requirements of all filtration systems.

[0024] 8. Also suitable for filtering solid particles: Nanofiber membrane can not only remove oil aerosol particles, but also has a higher filtration efficiency for solid particles, and can effectively remove various solid aerosol particles such as solid aerosol, dust, mist, smoke, chemical smoke and soot.

[0025] 9. Filter efficiency regeneration method: Mechanical charging, including external mechanical pressure such as slapping, rolling, sliding, etc. These methods can achieve charge regeneration without adding additional chemical reagents.

[0026] 10. Application scenarios of filter materials: The nanofiber membrane of the present invention has wide applicability and can be used to filter various solid and oil aerosols, and is suitable for preparing various filter products such as masks, air filters, filter bags, etc.

[0027] The present invention introduces a nanofiber oil-gas separation membrane material with mechanical regeneration capability, which uses two polymers with positive electron affinity and negative electron affinity, mixes them in the same solution, and prepares a nanofiber membrane through electrostatic spinning and other technologies. The obtained nanofiber membrane can enrich static charge in large quantities. Due to the large difference in surface energy between the two polymers, one polymer material (such as the positive electron affinity material) tends to be distributed inside the fiber, while the other polymer (such as the negative electron affinity material) is concentrated on the surface of the fiber. The interaction between the two polymers will cause a larger dipole moment, and the uneven distribution of the two materials in the fiber skin and core makes one charge tend to be distributed on the surface and the other charge is distributed inside, thereby greatly improving the static density on the fiber surface. In addition, by regulating the ratio of the two polymers inside the fiber, the diameter of the nanofiber and the surface density of the nanofiber membrane, the charge on the fiber surface can be further increased, so that the nanofiber membrane shows a high filtration efficiency for oil aerosol. In addition, the nanofiber membrane of the present invention can be regenerated by mechanical action after the charge is dissipated. By directly applying an external force to the nanofiber membrane, contact friction occurs between the different components on the internal nanofibers, and the friction process leads to the generation of charges on the fiber surface. Compared with nanofibers prepared from a single polymer material, the blended nanofiber membrane of the present invention can generate a larger charge density under the same mechanical action, so that the nanofiber membrane can restore the high filtration performance of oil aerosols. Therefore, the nanofiber membrane prepared by the present invention not only has the ability to efficiently filter oil aerosols, but also has excellent reusability. The invented nanofiber oil and gas separation membrane material is suitable for ventilation systems in industrial production, pharmaceuticals, medical and other places, as well as personal protection and natural gas transmission and other application scenarios, and has broad application prospects.

[0028] The present invention solves three key problems of electret filter materials, which are specifically listed as follows.

[0029] 1) How to increase the electrostatic charge of electret materials.

[0030] The filtration efficiency of the electret filter comes from the static charge it carries. Increasing the static charge of the electret material can not only enhance the filtration effect, but also extend the service life of the filter. At present, the most effective way to increase the charge of the material is to optimize the corona discharge parameters, including voltage, time and corona equipment structure. Although the corona discharge process can quickly increase the charge on the surface of the material, the stability of the charge is not ideal, and the ozone generated during the discharge process may have an impact on the environment. In addition, the charge of the fiber material can also be increased by friction electret (including hydroentanglement, needle punching and other methods), but these methods have limited effect on the increase of charge, and the process is complex and the cost is high.

[0031] Electrospinning is another method for preparing electret materials. In this process, the solution is stretched into fibers under the action of the electric field force, and a large amount of induced charges are formed on the fiber surface. Electrospinning technology has become an ideal choice for preparing nanofibers due to its advantages such as low cost, simple operation and structural controllability. These nanofibers are widely used in the manufacture of electret fiber filters due to their rich surface charges. However, traditional electrospinning usually uses a single polymer, resulting in a limited amount of charge carried. Although adding organic fillers or inorganic nanoparticles to the electret material can increase the charge and thus improve the filtration performance, the uneven distribution of the filler may affect the filtration efficiency. Therefore, how to effectively increase the electrostatic charge of nanofibers remains a challenge that needs to be solved.

[0032] 2) How to regenerate the charge.

[0033] As the use time increases, the static charge in the electret material tends to decay rapidly. To solve this problem, charge regeneration technology based on the principle of triboelectricity is integrated into the nanofiber membrane. During the friction process, two materials with different electron affinities can generate and maintain static charges through frequent contact and separation. This method can not only maintain the high filtration efficiency of the fiber filter, but also enhance its recycling capacity. Usually, the electret filter using the triboelectric effect is prepared by stacking assembly, which relies on mechanical action to achieve contact and separation of the friction layer during operation to achieve charge regeneration. However, the friction effect of this layered filter is extremely dependent on the design and optimization of the layered structure. In addition, these filters are insufficient in filtering capacity when facing large-area application scenarios, such as ventilation systems in factories, hospitals and other places.

[0034] Therefore, developing a nanofiber filter that does not rely on complex structural design and can self-generate charges through the triboelectric effect will help overcome the limitations of existing technologies and broaden their application range. This new filter will be able to meet the filtration needs of a wider range of industrial and medical environments, providing a more efficient, economical and environmentally friendly solution.

[0035] 3) How to make the regenerative charge work on oil aerosol.

[0036] The diameter of aerosol particles is between 0.01-10μm. Generally, commercial filters have difficulty in effectively removing aerosol particles of 0.3-1μm. It is generally believed that electret filters show significant effects on solid aerosol particles, and can restore their filtering efficiency for solid particles through friction. However, for the filtration of liquid particles (such as oil aerosols), the effect of electret filters is not ideal. To date, there has been no literature or patent report mentioning whether it is possible to use strong electret properties to achieve efficient filtration of oil aerosols, and to restore the filtering efficiency of electrets for oil aerosols through friction. If this performance can be achieved, it will have a significant impact on the filtration technology of oil aerosols.

[0037] The present invention introduces a nanofiber oil-gas separation membrane material with mechanical regeneration capability and its manufacturing process (see Figure 1 ). The two polymer mixed solutions are processed into nanofibers through electrostatic spinning technology. During the spinning process, the electrostatic field generates a large amount of induced charges on the surface of the nanofibers, and the blending of the polymers and the non-uniform distribution of the two polymers on the surface and inside the fiber effectively increase the electrostatic charge density of the nanofibers. This interaction greatly enhances the filtration efficiency of the nanofiber membrane for oil mist. In addition, after the charge of the prepared nanofiber membrane is dissipated, the charge can be regenerated through mechanical action. This regenerated charge significantly improves the filtration efficiency of oil particles. Therefore, this technology makes the nanofiber membrane not only highly efficient in oil mist filtration, but also has excellent reusability. Compared with the prior art, the present invention has the following beneficial effects: 1) Blended nanofibers increase surface charge: The coexistence and microphase separation of polymers in nanofibers cause the uneven aggregation of different polymers on the outside and inside, which effectively increases the surface potential of nanofibers, that is, leads to an increase in the amount of charge in nanofibers; 2) Excellent mechanical regeneration charge enhances oil mist filtration ability: Through mechanical charging, the nanofiber membrane can quickly restore the surface charge after the charge is completely removed. Therefore, after filtering oil mist for a long time, the nanofiber membrane can restore the high filtration efficiency of oil mist after mechanical charging; 3) Single-layer nanofiber membrane has an endogenous triboelectric effect: the nanofiber membrane does not require complex structural design and can be directly charged mechanically, which has wider applicability and practicality; 4) Diversity of filtration pollutants and wide range of applicable scenarios: The nanofiber membrane of the present invention can filter most pollutants including oil aerosols, salt aerosols, dust and smoke, and is suitable for compressor oil removal, ventilation systems in high-cleanliness places, air conditioning filters and other scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1The manufacturing process of nanofiber oil-gas separation membrane material and the principle diagram of enhancing charge and improving oil-aerosol filtration efficiency; Figure 2 The filtration efficiency and pressure drop (wind speed 33.3 L / min) of PVDF-PSF nanofiber membranes with different ratios (PSF content 0-100%) for 0.3 μm oil particles; Figure 3 (a) Surface potential of PVDF-PSF nanofiber membranes with different ratios (PSF content 0-100%); (b) Surface potential of PVDF-PSF nanofiber membranes (PSF content 50%) before and after charge removal and after charge recovery; Figure 4 (a) Filtration efficiency of PVDF-PSF nanofiber membrane (PSF content 50%) before and after charge removal and after charge recovery, where the small figure shows the filtration efficiency of the nanofiber membrane for oil particles with a diameter range of 0.3-1.5 μm; (b) Filtration efficiency and surface potential after charge regeneration treatment; Figure 5 The surface potential of the PVDF nanofiber membrane before and after charge removal and after charge recovery; Figure 6 The filtration efficiency and surface potential of pure PVDF nanofiber membrane after charge regeneration treatment; Figure 7 The surface potential of the PSF nanofiber membrane before and after charge removal and after charge recovery; Figure 8 Filtration efficiency and surface potential of pure PSF nanofiber membrane after charge regeneration treatment. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0040] In the following examples, all the raw materials used are common commercially available products that can be directly purchased.

[0041] Room temperature refers to 25±5°C.

[0042] Embodiment 1: (1) Preparation of PVDF-PSF (polyvinylidene fluoride-polysulfone) mixed solution PVDF and PSF are dissolved in a mixed solvent consisting of DMF and THF (the volume ratio of DMF and THF is 7:3) to obtain a polymer solution. The dissolution temperature of the polymer is about 60°C. The mass ratio of PVDF and PSF in the polymer solution is between 10:0 and 0:10, and the concentration of the polymer solution is 50% (mass percentage).

[0043] (2) Preparation of PVDF-PSF nanofiber membrane The completely dissolved and evenly mixed polymer solution is electrospun using an electrospinning device (the electrospinning device can be conventional equipment in the field, and its structure is not the innovation of this application, so it will not be repeated here), and the nanofibers are collected using a roller collector (rotation speed 300 rpm). During the electrospinning process, the applied voltage, the flow rate of the polymer solution and the spinning distance are 20 kV, 1 mL / h and 10 cm, respectively. Electrospinning is carried out under environmental conditions of a temperature of 25°C and a relative humidity of 30%. The thickness of the nanofiber membrane is controlled by the electrospinning time. The electrospinning time is 1 h, and the thickness of the nanofiber membrane is about 30 μm.

[0044] (3) Filtration performance test: The oil mist filtration performance was evaluated using an automatic filter tester (AFC131, TOPAS, Germany) and DEHS aerosol particles ranging from 0.2 μm to 4.59 μm. The diameter of the filter was 150 mm (test area, 225 cm 2 ). During the test, the air velocity was set to 33.3 L / min. Each test was repeated 3 times, and the filtration efficiency (η) and pressure drop (∆P) were the average values ​​of the tests. The following mainly gives the filtration test results of 0.3μm DEHS aerosol particles.

[0045] (4) Mechanical regeneration filtration capacity test: In order to regenerate the charge, the exhausted nanofiber membrane was repeatedly compressed (15 N, 1 Hz) by a mechanical device for 10 min. The nanofiber membrane was subjected to 10 filtration tests each time (5 min each time). Before the test, the nanofiber membrane was pre-rinsed with ethanol 10 times and then dried at room temperature. This process was set as one cycle. The cyclic test of the nanofiber membrane was performed for a total of 5 cycles.

[0046] (5) Experimental results.

[0047] (5.1) Filtration performance.

[0048] Figure 2 The effects of different ratios of PVDF-PSF nanofiber membranes (PSF content 0-100%) on the removal of 0.3 μm oil particles PM are given. 0.3 Filtration efficiency and pressure drop (wind speed 33.3 L / min). It can be seen from the figure that the filtration efficiency (η) gradually increases with the increase of PSF content in the nanofibers, until the PSF content reaches 60%, η reaches a maximum value of 99.1%. However, with the further increase of PSF content, the η of the nanofiber membrane gradually decreases (see Figure 2). For the PVDF-PSF blended nanofiber membrane, when the PSF composition increases from 0 to 50%, the pressure drop (∆P) hardly changes. However, when the PSF composition increases from 50% to 60%, ∆P increases from 27 Pa to 54 Pa. When the PSF content continues to increase, the pressure drop ∆P gradually decreases.

[0049] (5.2) Surface potential: Figure 3 The following table shows the surface potentials of (a) PVDF-PSF nanofiber membranes with different proportions (PSF content 0-100%) and (b) PVDF-PSF nanofiber membranes (PSF content 50%) before and after charge removal and charge recovery. It can be seen from the figure that as the PSF content increases, the value of the negative surface potential gradually increases. When the PSF content is 60%, the negative surface potential reaches a maximum value of -343.14 V (see Figure 3 ); and then as the PSF content continued to increase, the negative surface potential gradually decreased. After charge removal, the negative surface potential of the PVDF-PSF nanofiber membrane (PSF content 50%) dropped from -272.8 V to about -7.5 V. However, after charge regeneration treatment, the surface potential became -181.89 V.

[0050] (5.3) Filter regeneration performance: Figure 4 The filtration efficiency of PVDF-PSF nanofiber membrane (PSF content 50%) before and after charge removal and after charge recovery is given; (b) The filtration efficiency and surface potential after charge regeneration treatment. 0.3 The filtration efficiency dropped to 65.5% ( Figure 4 ). However, the filtration efficiency recovered to 84.3% after charge regeneration treatment. When the PVDF-PSF nanofiber membrane was subjected to charge regeneration treatment (15 N and 1 Hz, continuous repeated compression for 10 minutes) after 50 minutes of continuous filtration (about 10 times) and 10 times of ethanol washing (about 100 seconds), η recovered to 89.5%, which was 23.9% higher than that of the nanofiber membrane without charge regeneration. After another four similar treatment cycles, the initial η of the PVDF-PSF nanofiber membrane remained at about 90%. During the cycle, the ∆P of the nanofiber membrane remained unchanged at about 27 Pa.

[0051] Example 2: Preparation of pure PVDF nanofiber membrane (1) Material preparation: PVDF is dissolved in a mixed solvent consisting of DMF and THF (the volume ratio of DMF to THF is 7:3) to obtain a PVDF solution. The dissolution temperature of PVDF is about 60°C. The concentration of the PVDF solution is between 0% and 100%.

[0052] The completely dissolved PVDF solution was electrospun using an electrospinning device. The nanofibers were collected using a roller collector (rotation speed 30 rpm). During the electrospinning process, the applied voltage, the flow rate of the PVDF solution, and the spinning distance were 20 kV, 1 mL / h, and 10 cm, respectively. The electrospinning was carried out under environmental conditions of 25 °C and 30% relative humidity. The thickness of the nanofiber membrane was controlled by the electrospinning time. The electrospinning time was 1 h, and the thickness of the nanofiber membrane was about 30 μm.

[0053] The performance test of the PVDF nanofiber membrane is the same as that of Example 1.

[0054] (2) Experimental results: (2.1) Filtration performance: Depend on Figure 2 It can be seen that the η of pure PVDF nanofiber membrane is 75.8% and the pressure drop (∆P) is 25Pa (see Figure 2 ).

[0055] (2.2) Surface potential: Figure 5 The surface potential of the PVDF nanofiber membrane before and after charge removal and charge recovery is given. It can be seen from the figure that the surface potential of the pure PVDF nanofiber membrane is -104.33 V ( Figure 5 ). After charge removal, the negative surface potential of the PVDF nanofiber membrane dropped to about -2.1 V. However, after the charge regeneration treatment, the surface potential became -70.15 V again.

[0056] (2.3) Filtration regeneration performance: Figure 6 The filtration efficiency and surface potential of pure PVDF nanofiber membrane after charge regeneration are given. It can be seen from the figure that after the PVDF nanofiber membrane removes the charge, PM 0.3 The filtration efficiency dropped to 60.5%. However, the filtration efficiency recovered to 66.8% after charge regeneration treatment. When the PVDF nanofiber membrane was subjected to charge regeneration treatment (15 N and 1 Hz, continuous repeated compression for 10 minutes) after continuous filtration for 50 minutes (about 10 times), η recovered to 66.9% ( Figure 6), which is 6.4% higher than that of the membrane without charge regeneration. After another four similar treatment cycles, the initial η of the PVDF nanofiber membrane remained at around 67%. During the cycling process, the ∆P of the nanofiber membrane remained unchanged at about 24Pa.

[0057] Example 3: Preparation of pure PSF nanofiber membrane (1) Material preparation: PSF is dissolved in a mixed solvent consisting of DMF and THF (the volume ratio of DMF to THF is 7:3) to obtain a PSF solution. The dissolution temperature of PSF is about 60°C. The concentration of the PSF solution is between 0% and 100%.

[0058] The completely dissolved PSF solution was electrospun using an electrospinning device. The nanofibers were collected using a roller collector (rotation speed 30 rpm). During the electrospinning process, the applied voltage, the flow rate of the PSF solution and the spinning distance were 20 kV, 1 mL / h and 10 cm, respectively. The electrospinning was carried out under environmental conditions of a temperature of 25 °C and a relative humidity of 30%. The thickness of the nanofiber membrane was controlled by the electrospinning time. The electrospinning time was 1 h, and the thickness of the nanofiber membrane was about 30 μm.

[0059] The performance test of the PSF nanofiber membrane is the same as that of Example 1.

[0060] (2) Experimental results (2.1) Filtration performance: Depend on Figure 2 It can be seen that the η of pure PSF nanofiber membrane is 70.9% and the pressure drop (∆P) is 8 Pa (see Figure 2 ).

[0061] (2.2) Surface potential: Figure 7 The surface potential of the PSF nanofiber membrane before and after charge removal and charge recovery is given. It can be seen from the figure that the surface potential of the pure PSF nanofiber membrane is +223.25 V ( Figure 7 ). After charge removal, the positive surface potential of the PVDF nanofiber membrane dropped to approximately +5.3 V. However, after the charge regeneration treatment, the surface potential became +40.5 V.

[0062] (2.3) Filtration regeneration performance: Figure 8 The filtration efficiency and surface potential of pure PSF nanofiber membrane after charge regeneration are given. It can be seen from the figure that after the PSF nanofiber membrane removes the charge, PM 0.3The filtration efficiency dropped to 29.6%. However, the filtration efficiency recovered to 43.7% after charge regeneration treatment. When the PSF nanofiber membrane was subjected to charge regeneration treatment (15 N and 1 Hz, continuous repeated compression for 10 min) after continuous filtration for 50 min (about 10 times) and then rinsed with ethanol 10 times (about 100 s), η recovered to 44.9% ( Figure 8 ), which is 15.3% higher than that of the membrane without charge regeneration. After another four similar treatment cycles, the initial η of the PSF nanofiber membrane remained at about 45%. During the cycle, the ∆P of the nanofiber membrane remained unchanged at about 8 Pa. Table 1 gives a detailed comparison of the filtration efficiency and pressure drop of PVDF-PSF with pure PVDF and pure PSF nanofiber membranes.

[0063] Table 1. Comparison of filtration efficiency and pressure drop of PVDF-PSF, pure PVDF and PSF nanofiber membranes In summary, the present invention prepares a polymer mixed solution into a single-layer nanofiber membrane with an intrinsic triboelectric effect by electrospinning and other technologies, which significantly increases the charge of the nanofibers. The nanofiber membrane does not require a complex structural design, achieves high removal efficiency and reusability of oil mist, and is suitable for large-scale industrial ventilation systems or environmental protection equipment.

Claims

1. A method for preparing a nanofiber oil-gas separation membrane material with mechanical regeneration function, characterized in that: The steps include: 1) Preparing a polymer solution: dissolving two or more polymers in an organic solvent to obtain a polymer solution; the polymers include a positron affinity material and a negative electron affinity material; 2) Preparation of nanofiber membrane: The polymer solution is prepared by electrospinning, melt blowing, solution airflow assistance, template synthesis, self-assembly or microphase separation to obtain the nanofiber membrane.

2. The method for preparing the nanofiber oil-gas separation membrane material with mechanical regeneration function as claimed in claim 1, characterized in that: The material with positron affinity includes one or more of polysulfone, nylon, and cellulose; the material with negative electron affinity includes one or more of polyvinylidene fluoride, polypropylene, and polyacrylonitrile.

3. The method for preparing the nanofiber oil-gas separation membrane material with mechanical regeneration function as claimed in claim 1, characterized in that: The mass ratio of the positron affinity material to the negative electron affinity material is 10:0-0:

10.

4. The method for preparing the nanofiber oil-gas separation membrane material with mechanical regeneration function as claimed in claim 1, characterized in that: The organic solvent is a mixture of N,N-dimethylformamide and tetrahydrofuran; the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 10:0-0:

10.

5. The method for preparing the nanofiber oil-gas separation membrane material with mechanical regeneration function as claimed in claim 1, characterized in that: In step 1), the concentration of the polymer solution is 1-70%.

6. The method for preparing the nanofiber oil-gas separation membrane material with mechanical regeneration function as claimed in claim 1, characterized in that: The electrospinning in step 2) is specifically as follows: the nanofibers are collected using a roller collector, and during the electrospinning process, the applied voltage, the flow rate of the polymer solution and the spinning distance are between 1-50 kV, 1-5 mL / h and 1-20 cm, respectively.

7. The method for preparing the nanofiber oil-gas separation membrane material with mechanical regeneration function as claimed in claim 6, characterized in that: The thickness of the nanofiber membrane is between 10 μm and 1 mm. The electrospinning is carried out under the environmental conditions of temperature 10-65°C and relative humidity 10-50%, and the electrospinning time is 1-5 h.

8. A nanofiber oil-gas separation membrane material with mechanical regeneration function prepared by the preparation method according to any one of claims 1 to 7.

9. A method for regenerating the nanofiber oil-gas separation membrane material with mechanical regeneration function as claimed in claim 8, characterized in that: The nanofiber membrane is repeatedly compressed under the conditions of a pressure of 1-100 N and a frequency of 1-100 Hz for a compression time of 0.1-1 h.

10. The regeneration method of the nanofiber oil-gas separation membrane material with mechanical regeneration function as claimed in claim 9, characterized in that: The nanofiber membrane was pre-rinsed with ethanol for 10-100 times, dried at room temperature, and then compressed repeatedly.

Citation Information

Patent Citations

  • Recyclable electret filtering membrane and preparation method and cleaning and charge regeneration method thereof

    CN114504951A

  • Adaptive fabric for energy harvesting and filtering

    CN117083425A

  • Electrospun nanofiber polymer membranes for air filtration applications

    CN118451226A

  • Hydrophobic film with self-cleaning function, preparation method thereof and application thereof

    CN105002656A

  • Method for manufacturing electrospun nanofiber gas filtering material in mass manner

    CN105133187A